Taxonomic studies on Harnischia complex from India (Diptera: Chironomidae) - Mukherjee, Bindarika; Hazra, Niladri (Zootaxa, 2023)
Beckidia Sæther, 1979, Kloosia Kruseman, 1933, Parachironomus Lenz, 1921 and Saetheria Jackson, 1977 of the Harnischia complex are four newly recorded genera in India. Beckidia inflata sp. n., Kloosia incurva sp.n., Parachironomus salsus sp.n., Saetheria circinata sp.n., and Harnischia bulbosa sp.n. are described and illustrated. Microchironomus ishii Sasa, 1987, as a new record, is re-described and illustrated based on males. Three species, Paracladopelma nigrotibia (Bhattacharya, Dutta & Chaudhuri, 1985), Cryptotendipes acutus (Goetghebuer, 1936), and Saetheria sacculifera (Chaudhuri & Chattopadhyay, 1990) are proposed here as new combinations. Other Indian species of little known genera within the Harnischia complex are also re-examined and synonymisation is made. Molecular barcodes of five new species Beckidia inflata sp.n., Kloosia incurva sp.n., Parachironomus salsus sp.n., Saetheria circinata sp.n., and Harnischia bulbosa sp.n. and three known species of the Harnischia complex are also provided. Separate world keys of adult males of five genera are also designed here.